2020
DOI: 10.1016/j.sna.2019.111701
|View full text |Cite
|
Sign up to set email alerts
|

Electronic textiles based wearable electrotherapy for pain relief

Abstract: Electrotherapy device Highlights • A fabric electrode has been fabricated using the combination of weaving and printing technologies. • The conductive yarn pattern was optimized (2.5mm by 2.5mm grid) to achieve even current distribution of the electrode layer. • Asymmetric centrifugal mixing can breakdown the carbon particles and produce a high density (without voids) electrode. • The wearable electrotherapy was comfortable to wear and easy to use. • The prototype has been tested on six volunteers with osteoar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 12 publications
0
56
0
Order By: Relevance
“…However, these gel electrodes demonstrate reduced performance over time due to moisture evaporation and contamination build-up [46], rendering them unsuitable for long-term wearable applications. Fabric-based dry electrodes exist for wearable therapeutics and have been used in many applications including pain relief [47], stroke rehabilitation [48], [49], improving lymphatic function, and in treatment of urinary incontinence [50]. Materials suitable for making fabric electrodes include conductive yarns, silver polymer paste, and carbon polymer paste [46]- [50].…”
Section: A Physiological Sensors and Actuatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these gel electrodes demonstrate reduced performance over time due to moisture evaporation and contamination build-up [46], rendering them unsuitable for long-term wearable applications. Fabric-based dry electrodes exist for wearable therapeutics and have been used in many applications including pain relief [47], stroke rehabilitation [48], [49], improving lymphatic function, and in treatment of urinary incontinence [50]. Materials suitable for making fabric electrodes include conductive yarns, silver polymer paste, and carbon polymer paste [46]- [50].…”
Section: A Physiological Sensors and Actuatorsmentioning
confidence: 99%
“…The electrode can be printed on a thermoplastic film and transferred on to the textile via applied heat and pressure (Figure 2b). Alternatively, it can be printed on textile directly by printing all functional materials layer by layer [47] (Figure 2c), or a combination of the two methods above. An example of such a hybrid fabrication method is to weave the conductive yarn to form the base of the textile and the conductive path; then print the carbon electrode layer on top [48] (Figure 2d).…”
Section: A Physiological Sensors and Actuatorsmentioning
confidence: 99%
“…Gniotek et al 57 reported preliminary results, and the same project was continued with changed parameters in a later publication by Frydrysiak et al 61 Similarly, Curteza et al 35 and Poboroniuc et al 37 reported different aspects of the same study. Finally, the study by Liu et al 41 was a follow-up to an investigation by Yang et al 52 involving related electrode constructions, and Crema et al 60 applied an electrode manufacturing technology developed by Popovi c-Bijeli c et al 62 However, as these articles still offered different information, they were all considered in the review. In addition, a literature review article by Keller and Kuhn 20 provided supplementary information for the study performed by their extended research group in Keller et al 63 Thus, a total of 19 independent studies were reviewed with information retrieved from 23 publications.…”
Section: Selection Processmentioning
confidence: 99%
“…For dry textile electrodes, on the other hand, no clear consensus exists regarding their electrical performance. Some researchers have successfully proven that textile electrodes can also be used dry [ 8 , 35 , 37 ], while others prefer the use of textile electrodes in wet condition [ 6 , 24 , 25 , 26 , 31 , 32 , 33 , 34 ]. Nevertheless, dry electrodes are expected to provide advantages during usage; for example, a better user compliance is enabled when no re-wetting is required, the user comfort is improved when omitting the need for an electrolyte, and problems due to drying-out are avoided.…”
Section: Introductionmentioning
confidence: 99%